Laparoscopic management of adnexal masses: a hospital-based study - Bhattacharjee, Somen; Sharma, Shashi Shankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Laparoscopy is a widely used procedure in gynecological cases both for diagnostic and operative purposes. Laparoscopic surgery has been associated with early recovery, shorter duration of hospital stay and significant patient satisfaction. The present study is conducted to evaluate the effectiveness and safety of laparoscopy in the management of adnexal masses. Primary aim of this study is to find out the indications, intraoperative findings and the different interventions contemplated to deal with the adnexal masses. Methods: The study period was of 7 months, from July 2017 to January 2018, in the Dept of Obstetrics and Gynecology, MGM Medical College and M.Y. Hospitals Indore, MP. During this period, 63 patients underwent laparoscopy for various adnexal masses. Cases were critically analyzed and results were presented. Results: Most of the patients were from the age-group 25-30 yrs. Most common indication was ovarian tumor of varied pathology. Most common surgical procedure performed was ovarian cystectomy. The most common histopathological finding was functional ovarian cyst. Only 3.1% of cases needed conversion to laparotomy for the completion of the procedure. Complication rate was minimal. Conclusions: Laparoscopy due to its lesser adverse effects, less postoperative pain, shorter stay in hospital, small erre-admission rates, better panoramic vision is considered more beneficial than laparotomy. Careful patient selection and availability of a experts should be taken into account. The current study is an over view of our experience in favor of laparoscopy in treatment of a large population of women with benign adnexal masses.